The Impact of Sharia Compliance and Service Quality on Customer Loyalty with Religiosity as a Mediating Variable - Zaerofi, Afif; Sukmara, Denden; Haryono, Yono (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The objective of this study is aimed at analyzing the impact of sharia compliance and service quality on the loyalty of Islamic bank customers in Bogor regency with religiosity as mediating variable. This study is quantitative in nature. By using stratified random sampling, there are 277 respondents as the research sample. Structural Equation Modeling (SEM) is approached to analize the data. The results of the study find that sharia compliance and religiosity partially impact on the loyalty but interestingly service quality has no significat impact on it. Furthermore, it is found that religiosity significantly mediates the influence of sharia compliance on the loyalty but does not mediate the impact of service quality on the loyalty.